Nutraceuticals and Physical Activity as Antidepressants: The Central Role of the Gut Microbiota - Sabrina Donati Zeppa; Fabio Ferrini; Deborah Agostini; Stefano Amatori; Elena Barbieri; Giovanni Piccoli; Piero Sestili; Vilberto Stocchi (MDPI AG, 2022)
Major depressive disorder (MDD) is a common mental illness. Evidence suggests that the gut microbiota play an essential role in regulating brain functions and the pathogenesis of neuropsychiatric diseases, including MDD. There are numerous mechanisms through which the gut microbiota and brain can exchange information in a continuous, bidirectional communication. Current research emphasizes the interexchange of signals influenced by the gut microbiota that are detected and transduced in information from the gut to the nervous system involving neural, endocrine, and inflammatory mechanisms, suggesting a relationship between oxidative stress and the pathophysiology of MDD via the hyperactivation of inflammatory responses. Potential sources of inflammation in the plasma and hippocampus of depressed individuals could stem from increases in intestinal permeability. Some nutraceuticals, such as specific probiotics, namely psychobiotics, polyphenols, carotenoids, butyrate, and prebiotics, have been demonstrated to exert an antidepressant activity, but most of them need to be metabolized and activated by gut microorganisms. By inducing changes in the gut microbiota composition, physical exercise might also exert a role in alleviating depression-like symptoms. The mutual relationships among nutraceuticals, exercise, and depression will be discussed, and the potential role of the gut microbiota as a therapeutic target to treat depression will be explored.